Factors Affecting Antenatal Care Visit Obedience during the Covid-19 Pandemic in Konawe District, Southeast Sulawesi - Ayut Merdikawati; Eka Nurjannah; Asti Melani Astari; Muladefi Choiriyah (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2022)
The Covid-19 pandemic impacts both the access and quality of health services resulting in many restrictions on almost all routine services—the coverage of antenatal care visits in Indonesian public health centers decreases. Research on the factors affecting antenatal care visits of pregnant women during the Covid-19 pandemic in the eastern Indonesian population is currently limited. This study aims to analyze the factors affecting ANC visits of pregnant women during the covid-19 pandemic. This research implements a cross-sectional design by conducting the study on the coverage area of Pondidaha Health Center, Konawe, in January 2021. Respondents fulfilling the criteria included pregnant women residing in Konawe, experiencing the third trimester of pregnancy (28−40 weeks), having a personal Maternal-Child Health book, and recording the pregnancy visit at Pondidaha Public Health Center or Integrated healthcare center. The exclusion criteria included a mother who did not complete the questionnaires. The data analysis implements the Spearman rank test. Forty-six respondents participating in this study (with most of Pondidaha's pregnant women) were found to have incomplete ANC visits. Factors affecting incomplete ANC visits included knowledge, attitude, health care system, and health workers' support. The result indicated that the level of knowledge, mothers' attitude, healthcare, and health workers' support significantly indicated the positive outcome of ANC visits during the COVID-19 pandemic. In conclusion, the level of knowledge exhibited the highest correlation to the obedience of ANC visits.